Automatic Identification System in Maritime Traffic and Error Analysis - Bošnjak, Rino; Šimunović, Ljupko; Kavran, Zvonko (Transactions on Maritime Science, 2012)
Automatic Identification System (AIS) is used for security of ships and ports, their identification and protection of marine environment. Correct installation of AIS device and integration with navigation equipment is of great importance for the correct functioning of the system. To increase system accuracy correct input of data to the system is significant. Correct data interpretation depends on seafarer’s ability to recognize errors. In order for the seafarer to get acquainted with the system as well as its advantages and disadvantages high-quality seafarer’s training in the use of AIS is of utmost importance. AIS is not a navigation aid, nevertheless it can be used as a device to facilitate navigation. In this paper the authors are analysing AIS errors and proposing measures for improvement of its functioning.